Diagnosis of Electric Injuries: Histopathological Examination - Guntheti, Bharath Kumar; Singh, Uday pal; Khaja , Shaik (Journal of Indian Academy of Forensic Medicine, 2014)
The biggest challenge for a Forensic Pathologist is in the diagnosis of electrocution. This study consists eleven cases of electrical shock, which were brought to Mamata General Hospital Khammam, Andhra Pradesh; from Sept 2007 to Oct 2008. The characteristic feature of electrocution being electric contact mark over the body was not present in all mostall cases. Some time it is difficult for Forensic Pathologist to obtain electric mark by histopathological examination. The diagnosis of electrocution is confirmed by histopathological changes in skin. In all cases identified as dead due to electrocution samples were collected, preserved and undertaken for histopathological examination. The main objective is histopathological examination could be an important aid in diagnosis of Electrocution, where the findings were suggestive of electrical injuries. Considering the histopathological changes, nuclear steaming, dermo-epidermal separation and coagulative necrosis were the commonest features in skin with electric contact mark.